The research of tactics of the competitive activity of the qualified sportswomen in long jumps - Гребенюк, Олег Вікторович (Slobozhanskyi Herald of Science and Sport, 2016)
Grebenyuk A. Purpose: to research features of competitive tactics of the qualified sportswomen in long jumps from the running start. Material & Methods: such methods were applied the in researches: analysis of scientific and methodical literature, pedagogical supervision, content analysis (analysis of protocols of competitions). Results of 152 jumpers in length, who executed 886 attempts, are analyzed for the solution of the stated purpose. Results: options of competitive tactics of the qualified sportswomen in long jumps are defined. It is established when studying tactics of conducting a competitive fight of the strongest sportswomen of the world that questions of tactics of competitive activity of sportsmen in hopping types become <a title="Показать примеры употребления" href="http://www.lingvo.ua/ru/Search/Translate/GlossaryItemExtraInfo?text=%d0%b0%d0%ba%d1%82%d1%83%d0%b0%d0%bb%d1%8c%d0%bd%d1%8b%d0%b9&translation=of%20current%20importance&srcLang=ru&destLang=en">of current importance at the present stage of the development of track and field athletics. Conclusions: the analysis of the obtained data demonstrates that it is necessary to adhere to such tactical option which testifies to need of achievement of the maximum result already in the first attempts, but at the same time to conduct an active fight before the last attempt.